EVALUASI PERENCANAAN ASET TETAP PADA BADAN KEUANGAN DAERAH (BKD) KABUPATEN BOLAANG MONGONDOW - Silvia Zahra Ishak; Hendrik Gamaliel; Lidia M. Mawikere (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to evaluate the fixed asset planning conducted by the Regional Financial Agency (BKD) of Bolaang Mongondow Regency, covering the stages of procurement, maintenance, utilization, disposal, and transfer of assets. The main focus of this research is to assess the effectiveness and alignment of the existing planning procedures with applicable regulations, as well as to identify the challenges encountered in regional asset management. The method used in this study is a descriptive qualitative approach, with data collection through in-depth interviews, observations, and documentation. Data were collected from various stakeholders at BKD Bolaang Mongondow Regency, including structural officials and staff directly involved in asset management. The results of the study indicate that although the fixed asset procurement planning at BKD aligns with the existing regulations, there are several obstacles in its implementation, such as budget and time limitations, which hinder the effectiveness of procurement. Furthermore, asset maintenance often does not run optimally due to limited budget and lack of skilled personnel. Asset utilization has also not been maximized, with some assets not being used for their intended purpose. The asset disposal process faces bureaucratic procedures and a lack of supporting information systems, which slow down the disposal process. Meanwhile, asset transfer faces administrative obstacles that delay the transfer or sale of unused assets. This research recommends improvements in the planning and implementation of fixed asset management, including increasing the use of technology and digital systems, enhancing coordination among departments, and addressing administrative and bureaucratic challenges in asset disposal and transfer. In doing so, the management of fixed assets at BKD Bolaang Mongondow Regency can become more efficient and optimal.